2015
DOI: 10.1186/s12933-015-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble RAGE and atherosclerosis in youth with type 1 diabetes: a 5-year follow-up study

Abstract: BackgroundAdvanced glycation end products (AGEs) play a role in the development of late complications and atherosclerosis in diabetes by engaging the receptor for advanced glycation end products, RAGE. Receptor binding leads to activation of the vascular endothelium and increased inflammation in the vessel wall. The soluble variants of the receptor, endogenous secretory RAGE (esRAGE) and the cleaved cell-surface part of RAGE, which together comprise soluble RAGE (sRAGE), are suggested to have a protective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
1
36
0
2
Order By: Relevance
“…However, whether daily glucose fluctuations influence procoagulant activity we cannot answer. It has previously been published from this cohort that the degree of atherosclerosis (carotid intima media thickness, cIMT) was only slightly increased in the diabetes group, which may explain the current results. Ten years of disease duration is relatively short, and at this low age children and adolescents are free from longstanding exposure from other vascular risk factors, demonstrated in our cohort by the absence of microvascular complications.…”
Section: Discussionsupporting
confidence: 42%
“…However, whether daily glucose fluctuations influence procoagulant activity we cannot answer. It has previously been published from this cohort that the degree of atherosclerosis (carotid intima media thickness, cIMT) was only slightly increased in the diabetes group, which may explain the current results. Ten years of disease duration is relatively short, and at this low age children and adolescents are free from longstanding exposure from other vascular risk factors, demonstrated in our cohort by the absence of microvascular complications.…”
Section: Discussionsupporting
confidence: 42%
“…Examples of recently published work demonstrate that in type 1 diabetic children, with increasing age, levels of total sRAGE and esRAGE declined, and were associated with carotid intima-media thickness [80]. Others showed that levels of sRAGE were inversely correlated with vascular calcification in hemodialysis subjects, in a manner independent of levels of S100A12 RAGE ligand [81].…”
Section: Glycation and The Receptor Axis – Biomarkers For Diabetes Amentioning
confidence: 99%
“…Several hypotheses exist, which try to describe the molecular, cellular and biochemical mechanisms of premature atherogenesis in diabetic patients, but all have failed to sufficiently explain this phenomenon. Proposed mechanisms include the harmful effects of advanced glycosylation end products, modification of low density lipoproteins by non-enzymatic glycosylation, lipoprotein retention in the arterial wall, enhanced oxidative stress, inflammation, endothelial dysfunction, and alterations in metabolism of vitamins and minerals [1][2][3][4][5] . In addition to these potential factors, it is necessary to consider the possible role of insulin in the process of atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%